Realismo, detalle y experiencia: acerca de la Historia verdadera de Bernal Díaz del Castillo - Añón, Valeria (Latinoamérica. Revista de Estudios Latinoamericanos, 2016)
The past and the different ways in which it is represented in Latin american early chronicles of the conquest of México has been a central issue in Latin american colonial studies in the last few decades. The ambivalent limit between fiction and history, the way in which these chronicles pronounce themselves, The different discursive traditions that constitute each plot are crucial. In this context, the True history of the conquest of new spain by Bernal Díaz del Castillo emerges as a paradigmatic case, especially regarding the way in which it is enunciated, the polemics that constitute its plot, the constant reference to the “true history” it is supposed to tell. due to these dimensions, this chronicle has been characterized often as “realistic”. the question we seek to answer in this article is: what do we really mean when we say that the True history… is a “realistic” text?